Planning to create a website for Arabic library and information departments | التخطيط لإنشاء موقع لأقسام المكتبات والمعلومات العربية - Hafez | حافظ, Abdu Rashid bin Abdu Aziz | عبد الرشيد بن عبد العزيز (King Fahad National Library | مكتبة الملك فهد الوطنية, 2024)
The enormous potential provided by the World Wide Web (the Internet) to serve educational and cultural purposes cannot be ignored, and the network has enabled educational institutions to provide quality service. Advanced, through which they were able to achieve their educational goals more effectively, and hence these institutions have no choice but to access the Internet, interact with it, employ it, and research the new roles that they can perform through the Internet. | ان الإمكانات الهائلة التي توفرها الشبكة العنكبوتية (الإنترنت) لخدمة الأغراض التعليمية والثقافيـــة لا يمكن تـجـــاهلها ، وقـــد مكنت الشبكــة المؤسسات التعليمية لتقـــدم خدمة نوعية متطورة استطاعت من خلالها أن تحقق أهدافها التربوية بفعالية أكبر، ومن هنا فإنه لا خيار أمام تلك المؤسسات سوى الولوج إلى الإنترنت والتفاعل معها وتوظيفها وبحث الأدوار الجديدة التي يمكنها القيام بها من خلال الإنترنت